Prevention and Management of Variceal Hemorrhage - Dong Hyun Kim; Jun Yong Park (International Journal of Hepatology)
Variceal hemorrhage is a common and devastating complication of portal hypertension and is a leading cause of death in patients with cirrhosis. The management of gastroesophageal varices has evolved over the last decade resulting in improved mortality and morbidity rates. Regarding the primary prevention of variceal hemorrhaging, nonselective β-blockers should be the first-line therapy in all patients with medium to large varices and in patients with small varices associated with high-risk features such as red wale marks and/or advanced cirrhosis. EVL should be offered in cases of intolerance or side effects to β-blockers, or for patients at high-risk for variceal bleeding who have medium or large varices with red wale marks or advanced liver cirrhosis. In acute bleeding, vasoactive agents should be initiated along with antibiotics followed by EVL or endoscopic sclerotherapy (if EVL is technically difficult) within the first 12 hours of presentation. Where available, terlipressin is the preferred agent because of its safety profile and it represents the only drug with a proven efficacy in improving survival. All patients surviving an episode of bleeding should undergo further prophylaxis to prevent rebleeding with EVL and nonselective β-blockers.